Pengaruh Non-Performing Loan dan Loan to Deposit Ratio terhadap Cadangan Kerugian Penurunan Nilai - Siti Alawiyah Vebriana; Diharpi Herli Setyowati; Ade Ali Nurdin (Indonesian Journal of Economics and Management, 2020)
The main activity of the bank is to collect and raise funds from third-party channels through credit. In practice, conventional banks are faced with bad debt problems. The Bank's effort to anticipate bad credit is by establishing reserve funds in the form of Loan Loss Provisions (CKPN). The effect of NPL and LDR on CKPN is important to study because it can Maintain good bank performance. The sample size in this study is 36 banks listed on IDX. The data analysis technique used in this study is panel data regression analysis technique followed by classical hypothesis testing. The results of this study show that NPL have a positive impact on CKPN. The regression test results show that LDR has a negative impact on CKPN. The results of NPL and LDR using F test were positive and significant for CKPN.